A distinctive Pb-Sn semi-solid additive manufacturing using wire feeding and extrusion. (August 2022) - Zhang, Qi; Li, Hao; Han, Bin; Huang, Ke; Fang, Xuewei; Chen, Zhen
Abstract: Based on the semi-solid forming technology, the semi-solid additive manufacturing platform was built in this study, and the forming process was carried out with Pb-Sn wire as raw material. The results showed that when z-axis moving distance of monolayer stacking is 4.2 mm, extruder head temperature reaches 240 °C and heating plate temperature reaches 160 °C, the microstructure is composed of spherical grains of Pb solid solution with average diameter of 13.4 μm and low melting point Sn phase distributed at the grain boundary, the corresponding overlap surface curvature is 0.429 mm −1 ; The macro morphology also showed the best characteristics with forming effective degree of 0.869 and forming layer height ratio of 1.004. The mechanical properties of semi-solid additive manufacturing sample with optimized processing parameters were tested, the vertical and horizontal tensile strength of the sample are 44.2 and 47.8 MPa respectively, and the elongation in the vertical direction of sample (29.1 %) is significantly higher than that (20.1 %) in the horizontal direction because of double necking phenomena, this deformation mechanical can be explained by the existence of several bonding areas in gauge segment and soft of bonding areas due to enrich of Sn. Finally, Pb-Sn parts with different shapes were formed. This study provides a basis for the further development of semi-solid additive manufacturing for aluminum. Highlights: A new semi-solid additive manufacturing platform for Pb-Sn alloy is built. Pb-Sn semi-solid additive manufacturing process parameter is optimized. Double necking deformation mechanical is proposed to explain the anisotropy of semi-solid additive manufacturing parts. Pb-Sn semi-solid additive manufacturing parts are formed with optimized parameters.